A Dual-Track Asset Recovery Model: Optimizing the Posthumous Forfeiture of Corruption Proceeds - Anang Suhartono; John Pieris; Aarce Tehupeiory; Hulman Panjaitan (CV. Social Politic Genius (SIGn), 2026)
The transition of national positive law following the enactment of Law Number 1 of 2023 and Law Number 20 of 2025 creates a doctrinal inconsistency arising from a legislative omission in determining the legal status of evidence when personal criminal prosecution (in personam) is extinguished by operation of law upon the death of a corruption suspect. This normative weakness is reinforced by the inherent limitation of the sequential system under Law Number 31 of 1999. Under this system, civil claims by the State Attorney may be initiated only after the criminal process has been terminated or can no longer proceed, thereby causing asset depreciation and creating a time interval that enables the dissipation of corruption proceeds. This study employs normative legal research with a conceptual approach as the primary approach and a statute approach as the supporting approach through prescriptive qualitative analysis. The findings propose a paradigmatic reconstruction toward a parallel-simultaneous system through a dual-track asset recovery model. Under this model, the proprietary status examination (in rem) may proceed independently without depending on the legal status of the person subject to criminal prosecution. This model strengthens balanced legal protection and due process of law by applying the evidentiary standard of a balance of probabilities. This study recommends accelerating the enactment of the Bill on Asset Forfeiture, adopting limited amendments to Law Number 31 of 1999 and Law Number 20 of 2025, and establishing an integrated asset recovery center to optimize the posthumous forfeiture of corruption proceeds and restore public trust in law enforcement.